(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article focuses on real estate tax benefits in all foreign countries, based on the fact that tax exemption for socially significant population and real estate is typical for almost all countries of the world. Also in recent years, tax reforms carried out by a number of developed foreign countries have been studied in order to increase the share of real estate tax in budget revenues and reduce the unfair distribution of the tax burden. Briefly, the article discusses the experience of foreign countries on the taxation of real estate, on the basis of which proposals and recommendations have been developed on the positive and problematic aspects of the application of real estate tax in the tax system of our country.